(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The proposed model for risk stratification and individualized surgical management of anterior abdominal wall hernias not only reduces the incidence of complications and recurrences but also significantly improves the immediate postoperative period: shortens the hospital stay, accelerates patient mobilization, and facilitates the return to daily activities.